THE INFLUENCE OF MEDIA PUBLICATIONS, ENVIRONMENTAL PERFORMANCE, LEVERAGE AND INDUSTRY TYPE ON CARBON EMISSION DISCLOSURE - Marheni; Holiawati; Endang Ruhiyat (ZILLZELL MEDIA PRIMA, 2025)
Carbon emissions are the release of carbon gas into the atmosphere, which can arise as a result of a company's operational activities. Disclosure of carbon emissions is a form of responsible practice for environmental aspects carried out by companies. However, there are still companies that do not disclose carbon emission disclosure items. This research aims to examine the influence of Media Publications, Environmental Performance, Leverage and industry type on Carbon Emission Disclosure in energy sector companies listed on the Indonesia Stock Exchange. This research uses an associative quantitative approach. The type of data used is secondary data obtained from www.idx.co.id and the company website. The population in this research is Energy Sector Companies Registered on the IDX for the 2019 - 2023 Period. Meanwhile, the sample for this research was determined using a purposive sampling method so that 20 sample companies were obtained. The analytical method used is Panel Data Model Regression analysis. Data analysis used EViews version 12. The results of this research show that Media Publications, Environmental Performance and Leverage influence Carbon Emission Disclosure, while Industry Type has no influence on Carbon Emission Disclosure. It is hoped that this research can be used as additional information in making investment decisions, especially on environmental performance variables that influence the disclosure of carbon emissions. The limitations of this research are shown by the Adj R-Squred size of 18%. Therefore, it is recommended that future researchers re-examine other factors that have the potential to be determinants of carbon emissions disclosure besides the research variables.